International society of sports nutrition position stand: energy drinks and energy shots - Andrew R. Jagim; Patrick S. Harty; Grant M. Tinsley; Chad M. Kerksick; Adam M. Gonzalez; Richard B. Kreider; Shawn M Arent; Ralf Jager; Abbie E. Smith-Ryan; Jeffrey R. Stout; Bill I. Campbell; Trisha VanDusseldorp; et al. (Taylor & Francis Group, 2023)
Position Statement: The International Society of Sports Nutrition (ISSN) bases the following position stand on a critical analysis of the literature regarding the effects of energy drink (ED) or energy shot (ES) consumption on acute exercise performance, metabolism, and cognition, along with synergistic exercise-related performance outcomes and training adaptations. The following 13 points constitute the consensus of the Society and have been approved by the Research Committee of the Society: Energy drinks (ED) commonly contain caffeine, taurine, ginseng, guarana, carnitine, choline, B vitamins (vitamins B1, B2, B3, B5, B6, B9, and B12), vitamin C, vitamin A (beta carotene), vitamin D, electrolytes (sodium, potassium, magnesium, and calcium), sugars (nutritive and non-nutritive sweeteners), tyrosine, and L-theanine, with prevalence for each ingredient ranging from 1.3 to 100%. Energy drinks can enhance acute aerobic exercise performance, largely influenced by the amount of caffeine (> 200 mg or >3 mg∙kg bodyweight [BW−1]) in the beverage. Although ED and ES contain several nutrients that are purported to affect mental and/or physical performance, the primary ergogenic nutrients in most ED and ES based on scientific evidence appear to be caffeine and/or the carbohydrate provision. The ergogenic value of caffeine on mental and physical performance has been well-established, but the potential additive benefits of other nutrients contained in ED and ES remains to be determined. Consuming ED and ES 10-60 minutes before exercise can improve mental focus, alertness, anaerobic performance, and/or endurance performance with doses >3 mg∙kg BW−1. Consuming ED and ES containing at least 3 mg∙kg BW−1 caffeine is most likely to benefit maximal lower-body power production. Consuming ED and ES can improve endurance, repeat sprint performance, and sport-specific tasks in the context of team sports. Many ED and ES contain numerous ingredients that either have not been studied or evaluated in combination with other nutrients contained in the ED or ES. For this reason, these products need to be studied to demonstrate efficacy of single- and multi-nutrient formulations for physical and cognitive performance as well as for safety. Limited evidence is available to suggest that consumption of low-calorie ED and ES during training and/or weight loss trials may provide ergogenic benefit and/or promote additional weight control, potentially through enhanced training capacity. However, ingestion of higher calorie ED may promote weight gain if the energy intake from consumption of ED is not carefully considered as part of the total daily energy intake. Individuals should consider the impact of regular coingestion of high glycemic index carbohydrates from ED and ES on metabolic health, blood glucose, and insulin levels. Adolescents (aged 12 through 18) should exercise caution and seek parental guidance when considering the consumption of ED and ES, particularly in excessive amounts (e.g. > 400 mg), as limited evidence is available regarding the safety of these products among this population. Additionally, ED and ES are not recommended for children (aged 2-12), those who are pregnant, trying to become pregnant, or breastfeeding and those who are sensitive to caffeine. Diabetics and individuals with preexisting cardiovascular, metabolic, hepatorenal, and/or neurologic disease who are taking medications that may be affected by high glycemic load foods, caffeine, and/or other stimulants should exercise caution and consult with their physician prior to consuming ED. The decision to consume ED or ES should be based upon the beverage's content of carbohydrate, caffeine, and other nutrients and a thorough understanding of the potential side effects. Indiscriminate use of ED or ES, especially if multiple servings per day are consumed or when consumed with other caffeinated beverages and/or foods, may lead to adverse effects. The purpose of this review is to provide an update to the position stand of the International Society of Sports Nutrition (ISSN) integrating current literature on ED and ES in exercise, sport, and medicine. The effects of consuming these beverages on acute exercise performance, metabolism, markers of clinical health, and cognition are addressed, as well as more chronic effects when evaluating ED/ES use with exercise-related training adaptions.